Do Petroleum Product Pump Prices Influence Economic Growth in Nigeria? An Empirical Analysis - Iwuoha, Jude Chukwunyere; Awoke, Florence Chigozirim; Ubah, Chiwuike (Journal of Empirical Studies, 2021)
This study examined the impact of fuel pump price adjustment and the causal relationship between fuel pump price adjustments and economic growth in Nigeria using secondary data extracted from the Central Bank of Nigeria annual report and National Bureau of Statistics publications spanning from 1980 - 2019. Descriptive statistics, unit root test, Johansen cointegration test, VECM and Granger causality test were employed to analyse the data. The result showed that a 1% increase in the prices of PMS and AGO increased economic growth by 0.014%, 0.038% and 0.018% respectively while AGO is reduced by 0.002%. Also the prices of PMS, AGO and DPK does not granger cause economic growth in Nigeria within the period under this study meaning that any macroeconomic policy that affects economic growth should be pursued independent of fuel pump prices as any policy aimed at influencing economic growth through pump price adjustments seems to be ineffective.